(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
The Study provides a comprehensive overview of the challenges and experiences encountered by prisoners within the criminal justice system, with a focus on the Women Jail in Ludhiana, Punjab. Through data collected from 208 women prisoners, various facets of their social profiles, crimes committed, access to legal aid, living conditions, and rehabilitation efforts were examined. Key findings include the prevalence of under-trial prisoners and the lack of utilization of government-provided legal aid. Furthermore, it discusses the challenges faced by pregnant prisoners and the provisions made for prisoners with children, emphasizing the importance of ensuring their well-being and development. Overall, this study provides valuable insights into the live experiences of women prisoners and underscores the need for comprehensive reforms to address the challenges they face. It advocates for the protection of prisoners' rights, access to legal aid, and the implementation of effective rehabilitation programs to support their successful reintegration into society upon release.